Direct Cardiac Epigenetic Reprogramming through Codelivery of 5′Azacytidine and miR-133a Nanoformulation - Muniyandi, Priyadharshni; Palaninathan, Vivekanandan; Hanajiri, Tatsuro; Maekawa, Toru (International Journal of Molecular Sciences, 2022)
Direct reprogramming of cardiac fibroblasts to induced cardiomyocytes (iCMs) is a promising approach to cardiac regeneration. However, the low yield of reprogrammed cells and the underlying epigenetic barriers limit its potential. Epigenetic control of gene regulation is a primary factor in maintaining cellular identities. For instance, DNA methylation controls cell differentiation in adults, establishing that epigenetic factors are crucial for sustaining altered gene expression patterns with subsequent rounds of cell division. This study attempts to demonstrate that 5′AZA and miR-133a encapsulated in PLGA-PEI nanocarriers induce direct epigenetic reprogramming of cardiac fibroblasts to cardiomyocyte-like cells. The results present a cardiomyocyte-like phenotype following seven days of the co-delivery of 5′AZA and miR-133a nanoformulation into human cardiac fibroblasts. Further evaluation of the global DNA methylation showed a decreased global 5-methylcytosine (5-medCyd) levels in the 5′AZA and 5′AZA/miR-133a treatment group compared to the untreated group and cells with void nanocarriers. These results suggest that the co-delivery of 5′AZA and miR-133a nanoformulation can induce the direct reprogramming of cardiac fibroblasts to cardiomyocyte-like cells in-vitro, in addition to demonstrating the influence of miR-133a and 5′AZA as epigenetic regulators in dictating cell fate.